Innovation et subalternité - Alessandro Mongili (Socio-anthropologie, 2021)
This article is focused on the specificities of innovation processes in Sardinia, a Mediterranean region considered as “backward”. Starting from the analysis of four cases of innovation, it examines the role of innovation policies in defining the processes of socio-technical change, as well as their link with development policies. The focus is on the rigidity of these processes in relation to the status of various participants. In this regard, the article emphasizes the importance of multiple marginalizations and highlights the usefulness of the concept of subalternity to better characterize them. It also discusses the origin of this concept both in the work of the Sardinian thinker Antonio Gramsci and in its recovery by the decolonial approaches.